SLALOM: A language for SLA specification and monitoring - Correia, A.; Brito e Abreu, F.; Amaral, V. (INForum 2011 - Simpósio de Informática, 2011)
IT services provisioning is usually underpinned by service level agreements (SLAs), aimed at guaranteeing services quality. However, there is a gap between the customer perspective (business oriented) and that of the service provider (implementation oriented) that becomes more evident while defining and monitoring SLAs. This paper proposes a domain specific language (SLA Language for specificatiOn and Monitoring - SLALOM) to bridge the previous gap. The first step in SLALOM creation was factoring out common concepts, by composing the BPMN metamodel with that of the SLA life cycle, as described in ITIL. The derived metamodel expresses the SLALOM abstract syntax model. The second step was to write concrete syntaxes targeting different aims, such as SLA representation in process models. An example of SLALOM’s concrete syntax model instantiation for an IT service supported by self-service financial terminals is presented.